Rancang bangun aplikasi sistem pengiriman barang pada PT Mandiri Jaya Medika Fatmawati - Eko Tri Asmoro; Munich Heindari Ekasari; Desy Diana; Sri Mardiyati (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2021)
In today's modern era, technological developments in the world are increasingly significant, especially in the field of data processing information technology. With the advancement of information technology processing data or information in an educational institution, now the research entitled “Design and Build of Goods Delivery System Applications at PT. Mandiri Jaya Medika Fatmawati”, which was designed with Java Netbeans IDE, XAMPP, and MYSQL as its database. The design of this goods delivery application program goes through several stages, namely: the requirements stage, the analysis stage, the design stage, the implementation stage, and the deployment stage. In the process of making research reports and collecting data, the authors use qualitative methods in the form of literature study, observation, and interviews conducted at PT. Mandiri Jaya Medika which is located in Fatmawati. To analyze this application, the author uses object-oriented analysis with Unified Modeling Language (UML). The author hopes that the design of this Goods Delivery Application can help the processes of transaction activities within the company and make it easier for employees to make reports on stock data, partner data, vehicle data, and goods data. So there is no need to use paper media anymore.